2018
DOI: 10.18203/issn.2454-5929.ijohns20183703
|View full text |Cite
|
Sign up to set email alerts
|

Role of high resolution computed tomography of temporal bone in preoperative evaluation of chronic suppurative otitis media

Abstract: <p class="abstract"><strong>Background:</strong> Chronic suppurative otitis media (CSOM) is a common condition seen in patients attending ENT department. The diagnosis of cholesteatoma is usually made on otologic examination. The necessity for HRCT imaging in an uncomplicated case is controversial. The objective was<strong> </strong>to evaluate preoperative HRCT temporal bone and to determine its’ usefulness in patients with Chronic suppurative otitis media (CSOM) undergoing surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
(17 reference statements)
5
6
0
Order By: Relevance
“…The sigmoid sinus plate was eroded in 16% of cases with sensitivity of 88.8% and specificity of 100%. This is in accordance with the study by Prakash and Tarannum and Chatterjee et al [5,23]. Erosion of the lateral semicircular canal with labyrinthine fistula was seen in 8% of cases with sensitivity of 100% and specificity of 95.8%.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The sigmoid sinus plate was eroded in 16% of cases with sensitivity of 88.8% and specificity of 100%. This is in accordance with the study by Prakash and Tarannum and Chatterjee et al [5,23]. Erosion of the lateral semicircular canal with labyrinthine fistula was seen in 8% of cases with sensitivity of 100% and specificity of 95.8%.…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with the findings by Tak and Khilnani who found 91% sensitivity and 100% specificity [19]. Malleus was the next most commonly eroded ossicle after incus, seen in 48% of cases with sensitivity of 88.8% and specificity of 92.8% which is correlating to the study by Prakash and Tarannum who found 89.4% sensitivity and 90.9% specificity [5]. Stapes was found to be eroded in 34% of cases with lower sensitivity of 77.2% but showing specificity of 100%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…One false positive was seen associated with mesotympanum soft tissue density (parstensa cholesteatoma ) which involved the tympanic segment of facial nerve. Studies 24 quoted that tympanic segment of facial nerve canal and part of vertical segment was most commonly missed due to the thin underlying bony floor. But mesotympanum soft tissue density usually makes it difficult to identify facial canal dehiscence due to the oblique orientation of scan and it is frequently difficult to locate the pathology 6,26 .…”
Section: Resultsmentioning
confidence: 99%
“…An investigation reported that preoperative CT temporal bone scan of patients with CSOM serves as an important guide in surgical approach for otolaryngologists, although there are limitations in the evaluation of the CT results in. 21 A study conducted concluded that HRCT of the temporal bone was useful in finding the location and extent of disease in patients with chronic suppurative otitis media. 22 Another research concluded that preoperative CT of Middle ear lesions being useful for surgery planning but some lesion may not be completely diagnosed by CT scan, and intraoperative assessment of surgical field is crucial.…”
Section: Discussionmentioning
confidence: 99%